Tobacco Quitting Intention Among Rural People Living at Narayanganj District, Bangladesh - Hossain, Md Nazmul; Rahman, Ashiqur; Affan, Abdullah; Sharower, Md Golam (International Journal of Human and Health Sciences (IJHHS), 2026)
Bangladesh is ranked among the top ten countries with the heaviest smoking burdens globally. The country has a high adult smoking prevalence, with an estimated 21.9 million adults currently using tobacco products. This study aims to determine the intention to quit tobacco and its related factors among rural people of Bangladesh. This descriptive, cross-sectional study was conducted from January to December of 2023, at Kutubpur Union under Narayanganj Sadar Upazilla of Narayanganj District, Bangladesh. A total of 385 adult male tobacco users from a participated in this study. We adopted a convenience sampling technique. More than half of the respondents (51.4%) expressed an intention to quit tobacco use within the next 12 months. Among the respondents 46.2% had tried to stop smoking in the past 12 months. In terms of smoking patterns, 45.5% of participants smoked 5-10 cigarettes per day and 24.4% also used smokeless tobacco. The initiation of smoking was predominantly at a young age, with 84.94% starting between 15-20 years old. Exposure to antismoking messages was common, with television being the primary source (66.8%), followed by social networks (19.7%). Knowledge of tobacco control laws was limited, with 53% of respondents reporting they were unaware of such laws. However, a majority (95.6%) had noticed the health warnings on cigarette packages. Regarding beliefs and social influences, most participants believed that cigarette smoking causes serious illness (77.1%). Family pressure to quit smoking was reported by 56.4% of respondents. In contrast, only a small fraction (13.8%) had ever received advice from a doctor to quit smoking. At the workplace, smoking was not allowed for 49.9% of the respondents, while 34% reported having no specific smoking rules. International Journal of Human and Health Sciences Vol. 10 No. 01 Jan’26 Page: 8-13